Short or long runs: An exploratory study of odor‐induced fMRI design. (2nd July 2019) - Han, Pengfei; Zang, Yunpeng; Hummel, Cornelia; Faria, Vanda; Hummel, Thomas
Abstract : Objective: Functional magnetic resonance imaging (fMRI) is a non‐invasive neuroimaging technique widely used in olfactory research. During a typical fMRI olfactory block‐design, one functional "run" refers to a combination of multiple blocks with continuous brain image acquisition. The current study investigated the length of functional runs on odor‐induced brain response signals (blood oxygen level dependent [BLOD]) within the primary and key secondary olfactory areas. Methods: Twenty‐five female adults (age range 19 to 30 years, mean age 25 years) underwent a block‐design fMRI measurement with odor stimulation. Twelve participants received the odor stimuli within a short run paradigm (six blocks in each 4‐minute run, eight runs in total), and 13 participants received the odor stimulation with a long‐run paradigm (12 blocks in each 8‐minute run, four runs in total). For each paradigm, two odors (peach and rose) were alternatingly presented between runs. Participants rated odor intensity and pleasantness at the end of each run. Ratings and fMRI data were analyzed for different subsections and compared between groups. Results: There was a higher level of brain activation in the insula and orbitofrontal cortex during the short‐run paradigm as compared to the long‐run paradigm. However, there was no difference for odor intensity or pleasantness ratings. Conclusion: The current study suggested the employment of short runs with multiple repetitions for odor stimulation during fMRI research. Level of Evidence: 3 Laryngoscope, 130:1110–1115, 2020